Investment in Human Capital and Efficiency - Stancikas, Edmundas Regimundas (Ekonomika, 2000)
Under the human capital theory education is an investment make not only by the individual or his/her family hut also by the government through financing the main part of the expenses. The return on investment of the individual is an increase in his/her salary or wages during the post-investment period. The return for the slate is growing GNP due to the increased productivity of educated individuals.Judging from overview of scientific research of education influence un work productivity and economic growth we can conclude that this influence is minor.The stress is put on the results of social usefulness of investment into human capital: decrease of unemployment and crime rate, positive influence on political life of the society and children development. It is recommended to solve the relationship of the individual who invests into human capital and the stale through funds of the studies.